Remdesivir May Be Associated with Acute Kidney Injury in Covid-10 Patients: A Cohort Study - Amani Amir, Syed Tajammul Ali, Farzana Adnan Sheikh, Maleeha Sadaf, Sadiqa Anwar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To assess the outcomes of coronavirus disease-2019 patients with acute renal damage who received remdesivir against placebo at a private hospital in Karachi, Pakistan. Methodology: At the COVID-19 ICU of Hussain Lakhni Hospital, a cohort study was conducted from July 2021 to February 2022. Male and female study participants with COVID-19 and acute renal injury ranged in age from 40 to 80. Remdesivir-treated individuals with COVID-19 acute kidney injury were exposed, but placebo-treated patients with COVID-19 acute kidney injury were not exposed. In-hospital mortality, elevated serum creatinine levels, and prolonged hospital stays were the results. The data was analyzed using SPSS version 23. Results: Patients who took remdesivir had a lower mortality rate than those who were placebo (32.2% vs 67.8%, OR=0.38, 95 percent CI=0.27-0.52), with a p-value of 0.001. Remdesivir was also associated with a shorter hospital stay (4.2% versus 95.8%, OR=0.005, 95 percent CI=.003-0.009) with a p-value of 0.001). However, increased serum creatinine revealed statistically insignificant differences between groups. The odds of in-hospital mortality were 0.376 times lower (AOR=0.376, 95 percent CI=0.275-0.514, p=0.0001) and the odds of a prolonged hospital stay were 0.030 times lower (AOR=0.030, 95 percent CI=0.012-0.074, p=0.001) in the remdesivir group than in the placebo group after controlling for covariates. Practical implication: In literature Remdesvir was associated with acute kidney injury (rise in serum creatinine ) and in many centres ,it was not used in patients with acute kidney injury although it has very beneficial effect in patients of severe covid pneumonia,many centres were not using it in patients of acute renal failure. in our study , rise in serum creatinine was not significant in remdesvir group in patient with acute kidney injury ,so remdesvir must not be withheld in this group of patients as it can decrease the severity of covid pneumonia and saves patients lives Conclusion: Remdesivir is an effective medicine in COVID-19 patients with acute renal damage in terms of in-hospital mortality and duration of stay. Keywords: Acute kidney injury, coronavirus, COVID-19, in-hospital mortality, kidney damage, remdesivir, renal function, serum creatinine